D1.13 Update of Impact Assessment Methodology - Hadjimitsis, Diofantos G.; Mettas, Christodoulos; Leventis, Georgios; Neocleous, Kyriacos (My University, 2022)
The present document constitutes the thirteenth (13) deliverable of EXCELSIOR’s WP1 Project Management and Coordination, entitled “Update of Impact Assessment Methodology”; and it constitutes the fourth report relevant to Task 1.4 ‘Impact Monitoring and Re-assessment’. The primary goal of revising the Impact Assessment methodology is to ensure that the overall and specific objectives of the EXCELSIOR project are in proper track towards their successful achievement. This task undertakes the revision of the proposed methodology for the impact monitoring of the different activities carried out by Eratosthenes Centre of Excellence (ERATOSTHENES CoE) and its partners through EXCELSIOR against a set of predefined quantified targets. This document builds on D1.12 “Impact Assessment Methodology” and D1.15 “Impact Assessment Report for RP 2” that were previously submitted by the consortium; and the document extends further revision of certain Key Performance Indicators (KPIs) by encompassing the external reviewers’ feedback, provided in the framework of the second periodic review of the EXCELSIOR project.
Keywords: Remote Sensing; EXCELSIOR; ERATOSTHENES Centre of Excellence